Duodenal duplication cyst presenting as bilious vomiting in a neonate - Bakhtawar Dilawar; La-Raib Hamid; Areeba Nadeem Pirzada; Muhammad Arshad (Elsevier, 2020)
A neonate presenting with bilious vomiting requires prompt evaluation and diagnosis. In addition to the common causes of duodenal obstruction in this age group, duodenal duplication cysts need to be considered a part of the differential diagnosis. They are rare congenital occurrences that may present as bilious vomiting in a newborn. We report a case of a 22-days old baby boy presenting with abdominal distention and bilious vomiting, with later imaging revealing a cystic lesion in second and third part of the duodenum. The diagnosis of duodenal duplication cyst was further confirmed intraoperatively and in subsequent histopathological examination. The literature was reviewed and the best approach to diagnosis and management of duodenal duplication cyst in neonates is discussed.